Study of Mixed Complexes of Sulphur Containing Amino Acids by Ionophoretic Method (M(II)-Methionine-Penicillamine System). - TEWARI, B.B.; MOHAN, DINESH; SRIVASTAVA., S.K. (Asian Journal of Chemistry, 2010)
The formation constants of different complex species of some metal ions viz., Hg(II), Be(II) and Ni(II) with methionine were determined electrophoretically at an ionic strength of 0.1 M perchloric acid and 35ºC. The investigations have also been extended to mixed ligand systems using methionine and penicillamine as primary and secondary ligand respectively. This technique is based on the movement of a spot of metal ion under an electric field with the complexants added in background electrolyte at pH 8.5. The stability constants of complexes, M(II)–methionine–penicillamine have been found to be 10.23, 11.20 and 9.03 (log K values) for Hg(II), Be(II) and Ni(II) complexes respectively.